Why do we need to pause.... / Nazima Versay Kudus - Versay Kudus, Nazima (Academy of Language Studies, 2023)
Pausing is necessary for a number of reasons. First, it allows us to take a break and rest, which is critical for our physical and mental health. When we pause, we allow ourselves time to recharge and restore our energy levels, which can help us return to our duties feeling more rejuvenated and focused Second, taking a momentary break from what we are doing allows us to take stock of our actions and engage in more in-depth contemplation of them. We are able to obtain a new perspective on our tasks and find areas in which we can improve or make adjustments if we take a step back and look at the wider picture. Finally, stopping can prevent burnout and alleviate stress When we consistently exert ourselves without taking pauses we might get overwhelmed and weary, which can lead to physical and psychological issues. Ways to pause There are many ways to pause and take a break, depending on one's preferences and circumstances. Getting up from your desk and taking a short stroll can be an excellent way to clear your head and get some fresh air. Spending a few minutes meditating, doing deep breathing techniques or engaging in the act of 'nothingness' can help decrease tension and promote relaxation. Listening to soothing music can help you relax and regain concentration. A brief sleep may be an excellent method to rejuvenate and increase your energy levels. Participating in a hobby or activity you like, such as painting, reading, or gardening, can help you disconnect from work and reenergise. Spending time with loved ones is a wonderful opportunity to take a break and interact with others. Concentrating on the present moment and being conscious of your thoughts and emotions might help you relax and reduce stress.